Commitment, character, and citizenship : religious education in liberal democracy - Alexander, Hanan A., 1953-; Agbaria, Ayman K. (Routledge research in education ;, 2012)
As liberal democracies include increasingly diverse and multifaceted populations, the longstanding debate about the role of the state in religious education and the place of religion in public life seems imperative now more than ever. The maintenance of religious schools and the planning of religious education curricula raise a profound challenge. Too much state supervision can be conceived as interference in religious freedom and as a confinement of the right to cultural liberty. Too little supervision can be seen as neglecting the development of the liberal values required to live and wor.